FAKTOR STRATEGIK KETERAMPILAN PENYELESAIAN SOAL HOTS IPA KELAS 8 SMP BATIK SURAKARTA. - Isnaini Maratus Sholihah; Bambang Sumardjoko; Sumardi; Ahmad Muhibbin; Sigit Haryanto (Jurnal Penelitian Pendidikan IPA, 2023)
This correlational quantitative research aims to examine the relationships among metacognition ability, literacy ability, and High Order Thinking Skills (HOTS) in Science problem-solving among eighth-grade students at Batik Surakarta Middle School in 2023. Utilizing a simple random sampling technique, 168 students were selected as the sample. Data on metacognitive abilities, literacy skills, and HOTS Science problem-solving skills were collected through questionnaires. The analysis employed multiple linear regression with SPSS 25. The findings indicate a positive and significant correlation between metacognition abilities and HOTS Science problem-solving skills (regression coefficient: 1.311, effective contribution: 78.9%, relative contribution: 81.1%). Additionally, there is a positive and significant relationship between literacy skills and HOTS Science problem-solving skills (regression coefficient: 0.192, effective contribution: 18.27%, relative contribution: 18.8%). Collectively, these two independent variables contributed 97% to the variance in HOTS Science problem-solving skills, while the remaining 3% was influenced by unexamined variables. This research emphasizes the importance of metacognition and literacy in enhancing students' HOTS Science problem-solving abilities